The ammonoids from the Grès du Kahla supérieur of Timimoun (Middle-early Late Tournaisian; Gourara, Algeria) - D. Korn; V. Ebbighausen; J. Bockwinkel (Fossil Record, 2010)
The ammonoids from two very prolific horizons in the upper Kahla Sandstone (Tournaisian, Early Carboniferous) of Timimoun (Gourara, Algeria) are described monographically. Nine new ammonoid species are introduced: Imitoceras altilobatum n. sp., Triimitoceras amplisellatum n. sp., Kazakhstania inequalis n. sp., Acrocanites imperfectus n. sp., Xinjiangites scalaris n. sp., and Becanites canalifer n. sp. from the North African Kazakhstania-Acrocanites Assemblage as well as Acrocanites recurvus n. sp., Becanites singularis n. sp., and Becanites inflateralis n. sp. from the Pericyclus-Progoniatites Assemblage. The first of these is one of the most diverse ammonoid faunas known from this time interval.doi:10.1002/mmng.200900009